From Convenience to Concern: Exploring AI Paraphrasing Tools in Academic Writing Practices across Indonesia - Badriyah Ulfah (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2025)
Increasing numbers of educational institutions are using artificial intelligence (AI) tools, especially paraphrasing software. This technology is beneficial; however, it also raises concerns about its potential impact on writing development, originality, and creative thinking in higher education. Therefore, this qualitative exploratory study examines perspectives and usage patterns of paraphrasing tools among 25 lecturers at universities from eight regions across five islands in Indonesia. It further explores how lecturers keep students engaged, encourage creative thinking, and maintain academic integrity when AI support is available. The data collection process employed open-ended questions, enabling participants to provide detailed accounts of their experiences with paraphrasing tools, frequency and duration of use, underlying motivations, and pedagogical strategies used to promote critical thinking. The results show that most participants believe paraphrasing tools can help overcome writer’s block and reduce excessive textual similarity in academic submissions. Nonetheless, participants expressed concerns about possible over-reliance, superficial revisions, and diminished idea generation, which could hinder the creation of original arguments and an authentic authorial voice. Participants therefore recommend project-based learning (PjBL), problem-based learning (PBL), authentic writing tasks, and a process-based approach, complemented by explicit guidance on ethical AI use. This study concludes that although AI tools can provide substantial support, lecturers should integrate them through pedagogies that emphasize authentic writing processes, reflective practice, and independent thinking. Therefore, universities should set clear AI-use policies and train lecturers to integrate paraphrasing tools through authentic, process-based PBL/PjBL to support originality, critical thinking, and academic integrity.